The Political Geography of the January 6 Insurrectionists - Pape, Robert A.; Larson, Kyle D.; Ruby, Keven G. (PS, political science & politics, 2024)
What are the local political, economic, and social conditions of the communities that sent insurrectionists to the US Capitol in support of Donald Trump? Using a new dataset of the home counties of individuals charged for the Capitol insurrection, we tested two prominent theories of electoral populism and support for populist leaders like Donald Trump—demographic change and manufacturing decline—and whether they also explain violent populism. We also examined the effects of local political conditions. We find that white population decline is a stronger predictor of violent populism and that counties that voted for Trump were less likely to fight for Trump. The effect of white population decline is even greater in counties whose US House Representative rejected the 2020 election results. These findings suggest scholars should resist assuming violent populism is merely an extension of electoral populism, and solutions to one will not necessarily remedy the other.